2020
DOI: 10.1038/s41368-020-00094-1
|View full text |Cite
|
Sign up to set email alerts
|

Study of Sr–Ca–Si-based scaffolds for bone regeneration in osteoporotic models

Abstract: Bone tissue engineering has emerged as a promising alternative therapy for patients who suffer bone fractures or defects caused by trauma, congenital diseases or tumours. However, the reconstruction of bone defects combined with osteoporosis remains a great challenge for clinicians and researchers. Based on our previous study, Ca–Si-based bioceramics (MSCs) showed enhanced bone formation capabilities under normal conditions, and strontium was demonstrated to be therapeutic in promoting bone quality in osteopor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 27 publications
0
11
0
2
Order By: Relevance
“…From the clinical point of view, new CS-based experimental material has certain advantages since Sr incorporation may enhance the bone healing during root end canal surgery by activating osteoblasts for improved bone synthesis [22,23,24]. In addition, if used for pulp capping procedures, it may stimulate odontoblasts for faster formation of tertiary dentine.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…From the clinical point of view, new CS-based experimental material has certain advantages since Sr incorporation may enhance the bone healing during root end canal surgery by activating osteoblasts for improved bone synthesis [22,23,24]. In addition, if used for pulp capping procedures, it may stimulate odontoblasts for faster formation of tertiary dentine.…”
Section: Discussionmentioning
confidence: 99%
“…Opšti cilj ove studije bio je da se dodatno poboljša kvalitet cementa ALBO MPCA dodavanjem potencijalno bioaktivnog radiokontrasta -stroncijum-karbonata (SrCO 3 ). Ideja je ukorenjena u dokazima brojnih povoljnih efekata stroncijuma (Sr) na kost i zubna tkiva, među kojima su osteoproliferativni i odontoproliferativni efekati, stimulacija formiranja kosti i angiogeneza, inhibicija ćelijske diferencijacije i osteoklastne aktivnosti, odnosno indukcija humanih stem ćelija zubne pulpe promocijom njihove odontogene diferencijacije, proliferacije i mineralizacije [22,23,24]. Cilj ovog istraživanja je bio da utvrdi minimalni udeo SrCO 3 kao rendgenkontrastnog sredstva koji zadovoljava zahteve ISO u dentalnim cementima i da proveri biokompatibilnost ovog materijala u kulturi ćelija L929.…”
Section: Acknowledgesunclassified
See 2 more Smart Citations
“…The antimicrobial properties can be further enhanced by appealing to different combinations [ 14 , 15 ]. Other authors [ 16 ] demonstrated the efficiency of Sr incorporation in osteoporotic bone regeneration. Overall, its favorable influences led to the production of materials belonging to different compositional or dimensional classes, including fibers [ 17 ], thin films [ 18 ] and composites [ 19 ].…”
Section: Introductionmentioning
confidence: 99%